The Condition of the Coronary Arteries in Patients with Ischemic Mitral Insufficiency - S. A. Rudenko; S. V. Potashev; O. V. Rudenko; V. P. Zakharova; O. K. Gogayeva; A. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2020)
Secondary (or functional) mitral regurgitation is the result of myocardial dysfunction due to ischemic injury with relatively normal cusps. In patients with ischemic mitral insufficiency, only surgical coronary artery bypass grafting can affect the reverse remodeling of the left ventricle and reduce the degree of mitral regurgitation. One of the main pathogenetic factors for the development of this type of mitral insufficiency is myocardial ischemia. Studying the state of coronary blood flow in patients with ischemic mitral insufficiency is a primary task in the surgical treatment of this pathology.The aim. To study the condition of the coronary arteries in patients with ischemic mitral insufficiency.Material and methods. From January 2015 to December 2019, 194 patients with ischemic mitral insufficiency underwent surgical intervention at the Amosov National Institute of Cardiovascular Surgery of the NAMS of Ukraine.Results and Discussion. Coronarography revealed haemodynamically significant coronary artery stenosis in 190 (97.9%) patients. In 4 (2.1%) patients there was no hemodynamically significant coronary arteries stenosis. Analysis of the data of selective angiography showed that the majority of patients with ischemic mitral insufficiency had three-vessel disease (75.2%). Occlusion of the left circumflex coronary artery was observed in 33 (17.4%), and sub-occlusive changes were detected in 3 (1.6%) of patients. A completely different lesion pattern is observed for the branches of the right coronary artery. Thus, in 56 (29.4%) cases, occlusion of a particular branch was found on angiogram. Sub-occlusion of the right coronary artery was observed in 15 (7.9%) cases.Conclusions. In patients with ischemic mitral insufficiency, hemodynamically significant stenosis was most often observed in the anterior interventricular artery (81.6%). Comparison of the status of the right coronary artery and circumflex artery showed that the right coronary artery lesions occurred more frequently. The section of the right coronary artery between the outflow of the acute marginal branch and the branching to the posterior interventricular and lateral branches was the most vulnerable site of the coronary bed, where the frequency of occurrence of critical stenosis was 28.4%.